A Novel Cervical Spinal Cord Window Preparation Allows for Two-Photon Imaging of T-Cell Interactions with the Cervical Spinal Cord Microvasculature during Experimental Autoimmune Encephalomyelitis - Haghayegh Jahromi, Neda; Tardent, Heidi; Enzmann, Gaby; Deutsch, Urban; Kawakami, Naoto; Bittner, Stefan; Vestweber, Dietmar; Zipp, Frauke; Stein, Jens V.; Engelhardt, Britta (Frontiers in Immunology, 2017)
T-cell migration across the blood-brain barrier (BBB) is a crucial step in the pathogenesis of experimental autoimmune encephalomyelitis (EAE), an animal model of multiple sclerosis (MS). Two-photon intravital microscopy (2P-IVM) has been established as a powerful tool to study cell-cell interactions in inflammatory EAE lesions in living animals. In EAE, central nervous system (CNS) inflammation is strongly pronounced in the spinal cord, an organ in which 2P-IVM imaging is technically very challenging and has been limited to the lumbar spinal cord. Here we describe a novel spinal cord window preparation allowing to use 2P-IVM to image immune cell interactions with the cervical spinal cord microvascular endothelium during EAE. We describe differences in the angioarchitecture of the cervical spinal cord versus the lumbar spinal cord, which will entail different hemodynamic parameters in these different vascular beds. Using T cells as an example we demonstrate the suitability of this novel methodology in imaging the post-arrest multi-step T-cell extravasation across the cervical spinal cord microvessels. The novel methodology includes an outlook to the analysis of the cellular pathway of T-cell diapedesis across the BBB by establishing visualization of endothelial junctions in this vascular bed.